Elements and requirements of the moral act - Bretoneche Gutiérrez, Luis Alberto (2021)
This article contains an analysis of the elements and requirements that intervene in the evaluation of the moral act, which are identified as a moral subject, moral community, moral norm, knowledge of the moral norm and moral sanction. In addition, examples of the elements that intervene in the qualification of the moral subject have been examined and placed, where fredom, physical and mental health, acting, responsability according to each specific situation and moral conscience appear. Depending on the, it can be appreciated when human acts are moral, inmoral, amoral or antimoral. To elucidate the issue, the knowledge, procedures and rational instruments of two philosophical disciplines, Axiology and Ethics, have been used, which always appear in the evaluation of all moral action.